2012
DOI: 10.1200/jco.2012.42.2907
|View full text |Cite
|
Sign up to set email alerts
|

Acute Myeloid Leukemia (AML): Different Treatment Strategies Versus a Common Standard Arm—Combined Prospective Analysis by the German AML Intergroup

Abstract: A strictly prospective comparison of different treatment strategies in patients with AML did not show clinically relevant outcome differences when compared through a common standard treatment arm. The results provide a representative basis for further therapeutic approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
86
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(91 citation statements)
references
References 21 publications
4
86
0
Order By: Relevance
“…As in allogeneic transplantation, veno-occlusive disease is an uncommon complication after an autograft using intravenous busulfan. Antonio Torres Gomez, 7 Simona Lapusan, 3 Giuseppe Irrera, 8 Jose E Guimaraes, 9 Aida Botelho Sousa, 10 Angelo M. Carella, 11 Norbert Vey, 12 William Arcese, 13 Avichai Shimoni, 1 Raanan Berger, 1 Vanderson Rocha, fan pharmacokinetics, an intravenous formulation of busulfan has recently been developed. In adults, intravenous busulfan has shown predictable and consistent pharmacokinetic profiles with acceptable toxicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in allogeneic transplantation, veno-occlusive disease is an uncommon complication after an autograft using intravenous busulfan. Antonio Torres Gomez, 7 Simona Lapusan, 3 Giuseppe Irrera, 8 Jose E Guimaraes, 9 Aida Botelho Sousa, 10 Angelo M. Carella, 11 Norbert Vey, 12 William Arcese, 13 Avichai Shimoni, 1 Raanan Berger, 1 Vanderson Rocha, fan pharmacokinetics, an intravenous formulation of busulfan has recently been developed. In adults, intravenous busulfan has shown predictable and consistent pharmacokinetic profiles with acceptable toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…1 Autologous hematopoietic stem cell transplantation (ASCT) offers an alternative possibility of delivering high-dose myeloablative treatment in AML. Several historical randomized trials have reported significantly lower relapse incidences after ASCT than after conventional chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts aimed at improving long-term survival of these patients thus have involved the fine-tuning of dosing within this framework, leading to adoption of 317 variants in recent years as attempts to intensify induction chemotherapy. Although escalation of ARA-C dosing is one of the most extensively explored avenues in clinical trials [10][11][12][13][14]27], results overall remain inconclusive [10][11][12][13][14]27]. One plausible explanation for conflicting evidence is that the efficacy of a given regimen, as reflected by survival estimates, may be influenced by the nature of post-consolidation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Two patients withdrew their consent before initiation of treatment; thus, a total of 93 patients are reported. Prior treatments of the patients were as follows: 29 patients received standard induction therapy with idarubicin, cytarabine, and etoposide (ICE), 26 patients ICE in combination with ATRA (A-ICE), 17 patients with valproic acid (V-ICE), and 12 patients with both ATRA and valproic acid (VA-ICE), according to the initial randomization of the AMLSG 07-04 protocol (clinicaltrials.gov identifier: 00151242); 28 9 patients were treated in the German AML Intergroup trial 29 and received standard induction therapy with daunorubicin and cytarabine (DA). Median age was 48 years (range 22-62 years); further demographics and baseline characteristics of the 93 patients are shown in Table 1.…”
Section: Patients' Characteristicsmentioning
confidence: 99%